Impact of dentofacial deformity on the chance of being hired for a job - de Miranda, Bruna Marlene; Gonçalez Miguel, Patricia Tavian; Gonçalves, Flavio Magno; Costa, Davani Latarullo; Bronholo, Thalita de Paris Matos; Guariza-Filho, Odilon; Stechman-Neto, José; Santos, Rosane Sampaio; Zeigelboim, Bianca Simone; de Araujo, Cristiano Miranda (Frontiers in Psychology, 2023)
Objective This study aimed to determine the impact of dentofacial deformity on an individual’s chances of being hired for a hypothetical job involving customer service. Materials and methods Face photographs (frontal and lateral) of 15 patients with moderate to severe dentofacial deformity, taken before and after orthodontic-surgical correction, were selected and randomized between two different questionnaires. In addition, five patients without dentofacial deformity were used as controls in both questionnaires. These questionnaires were taken by adults responsible for hiring personnel to work in commerce and business activities, graduates or postgraduates in business administration, with experience in recruiting and hiring personnel. The evaluation took place using a Likert scale with values ranging from 0 to 10 (in which 0 corresponded to complete disagreement and 10 to complete agreement), considering the following variables in a first impression judgment: honesty, intelligence, productivity at work, and hiring chance. Data were tabulated and statistical analysis was performed using a linear regression model for the explanatory variables that showed statistical significance in the analysis of variance (ANOVA). Effect size through Cohen’s d has been corrected for all comparisons performed. Results All re-examined domains demonstrated statistical differences even when included in a multivariate model (p < 0.05), with lower mean values for those requiring pre-treatment (presenting deformity), although the effect size was small for all comparisons. Conclusion Dentofacial deformity influenced the hiring chance, although not appearing to be a preponderant factor for hiring, acting as a tiebreaker among the candidates adopted.